2017
DOI: 10.24266/0738-2898-35.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of substrate and irrigation interval on the post-transplant root growth of container-grown zinnia and tomato1

Abstract: Substrate type and irrigation interval were studied to determine their impact on the post-transplant root growth of ‘Thumbelina' zinnia (Zinnis elegans Jacq.) and ‘Celebrity Hybrid' tomato (Lycopersicon esculentum Mill.). Seeds of both species were planted in 80 cm3 (2.7 fl oz) plug cells containing either Metromix 360™ (MM360) or Ball Professional Growing Mix™ (BPGM) and, following germination, the seedlings were transplanted into 450 cm3 (27.5 in3) plastic pots containing the same substrate. Evapotranspirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…or 96 h for tomatoes (Lycopersicon esculentum Mill.) showed significantly higher root parameters than similar transplants watered daily [53]. Similarly, Ismail and Ozawa [54] found that a 3-day irrigation interval showed a remarkably higher root development for chili pepper than 1 or 5 d treatments.…”
Section: Tomatomentioning
confidence: 88%
See 2 more Smart Citations
“…or 96 h for tomatoes (Lycopersicon esculentum Mill.) showed significantly higher root parameters than similar transplants watered daily [53]. Similarly, Ismail and Ozawa [54] found that a 3-day irrigation interval showed a remarkably higher root development for chili pepper than 1 or 5 d treatments.…”
Section: Tomatomentioning
confidence: 88%
“…The crosstalk between different nutrient signals and the benefits of RSA responses in a particular condition are yet to be characterized [43]. Primary root growth inhibition, increase in lateral roots and root hairs Various crops Various production system Limited P supply [39,41,46] Increase in vertical, deep roots Various crops Various production systems Limited N supply [40,43,47] Increased root dry weight, specific root length, root tissue density, and root length density due to increased irrigation intervals Tomato, Zinnia 450 mL plastic pots containing either Metromix 360 (MM360) or Ball Professional Growing Mix (BPGM) 24-h, 48-h, and 96-h irrigation intervals [53] Chili pepper 31 cm × 15 cm × 60 cm container filled with sandy-loamy soil 1-, 3-and 5-day irrigation intervals [54] When the growing system enables maintaining a constant concentration of each nutrient at the root surface, as is the case of NFT, DFT, and aeroponics, the ability of the restricted root system to meet plant requirements is not a limiting factor [12]. This is because frequent fertigation might improve the uptake of nutrients through the continuous replenishment of nutrients in the depletion zone at the vicinity of the root interface and enhance the transport of dissolved nutrients by mass flow [55].…”
Section: Nutrient Solutionmentioning
confidence: 99%
See 1 more Smart Citation